Activation of TLR signalling regulates microwave radiation‐mediated impairment of spermatogenesis in rat testis. (6th August 2017) - Wu, H.; Wang, D.; Meng, Y.; Ning, H.; Liu, X.; Xie, Y.; Cui, L.; Wang, S.; Xu, X.; Peng, R.
Summary: Microwave radiation could increase the expression of pro‐inflammatory cytokines in rat Sertoli cells, which may impair spermatogenesis. However, the mechanisms that microwave radiation induces the cytokine expression in Sertoli cells remain to be clarified. The activation of TLRs by their ligands can trigger a common signalling pathway to upregulate inflammatory cytokines such as IL‐1, IL‐6, IL‐12 and TNF‐α. Microwave radiation can increase the expression of TLRs in lymphocytes. The purpose of this study was to determine the effect of microwave radiation on the TLRs in rat testis. We focus on the effect of TLR2‐5 (which is expressed relatively highly) by microwave radiation. The results showed that the expression of TLR2‐5 and the pro‐inflammatory cytokines (IL‐1β, IL‐6 and TNF‐α) was increased both in mRNA and in protein. Furthermore, p‐p38, p‐ERK1/2, p‐JNK and p‐NF‐κB p65, the key factors of TLR signalling, were also elevated by microwave exposure. And the NF‐κB can be induced more dominantly. These results suggest that TLRs signalling can be activated by microwave radiation in testis, which may provide the molecular basis for the in‐depth study.